Student Engagement: Towards A Critical Policy Sociology. Issue 1 (March 2017) - Tomlinson, Michael
Abstract This article develops a critcal policy analysis of the student engagement agenda, exploring its establishment as a key policy framework in HE and why it has developed such momentum. Based on a critical policy sociology approach, this article analyses the levels through which student engagement can be conceptualised: macro, meso and micro. At the macro-level, the concept can be seen as partly aligned to the market-driven and massified institutional context and informed by New Public Management policy levers intended to enhance the performative value of contemporary universities. At the meso-level, student engagement has been instituted by policies and practices evaluated by a range of performance measures that purportedly capture the efficacy of engagement practices. At a micro-level, it presents issues around students' relationship with institutions in light of their changing role. If student engagement policy and practice is able to elevate students as active co-producers of self-directed learning, they may also potentially affirm their role as regulatory customers.